Management, outcomes and survival of an Australian IgG4‐SC cohort: The MOSAIC study. (3rd September 2021) - Kemp, William; Majeed, Ammar; Mitchell, Joanne; Majumdar, Avik; Tse, Edmund; Skoien, Richard; Croagh, Daniel; Dev, Anouk; Gao, Hugh; Weltman, Martin; Craig, Philip; Stuart, Katherine; et al.
Abstract: Background and Aims: IgG4 sclerosing cholangitis (IgG4‐SC) is the biliary component of the multisystem IgG4‐related disease. We aimed to investigate the clinical features, demographics, treatment response and outcomes of IgG4‐SC in a large Australian cohort. Methods: We conducted nationwide retrospective cohort via the Australian Liver Association Clinical Trials Network (ALA‐CRN). 39 sites were invited to participate. IgG4‐SC was defined by the clinical diagnostic criteria established by the Japanese Biliary Association in 2012. Data were collected on patient demographic, clinical and laboratory information, presenting features, response to therapy and clinical outcomes. Results: 67 patients meet inclusion criteria from 22 sites. 76% were male with mean age of 63.3 ± 14.5 years and a median IgG4 level of 3.6 g/L [0.09‐67.1]. The most frequent presenting symptom was jaundice (62%) and abdominal pain (42%) and Type 1 biliary stricturing (52%) at the distal common bile duct was the most frequent biliary tract finding. Prednisolone was used as a primary treatment in 61 (91%) and partial or complete response occurred in 95% of subjects. Relapse was common (42%) in those who ceased medical therapy. After a median follow up of 3.9 years there was one hepatocellular carcinoma and no cholangiocarcinomas. Conclusions: Our study confirms the preponderance of IgG4‐SC in males and highlights the steroid response nature of this condition although relapse is common after steroid cessation. Progression to malignancy was uncommon.